POTENSI KENTANG HITAM DALAM MEREDUKSI STRES OKSIDATIF DAN MENGHAMBAT PROLIFERASI SEL KANKER PAYUDARA MCF-7 [Potential of Black Potato in Reducing Oxidative Stress and Inhibiting the Proliferation of Breast Cancer Cells MCF-7] - Mutiara Nugraheni; Umar Santoso; . Suparmo; Hastari Wuryastuti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
The ethanolic extracts of flesh and peel of Coleus tuberosus were evaluated for its ability to reduce oxidative stress using cellular antioxidant activity testing on MCF-7 cells based on oxidation of 2.7-dichlorofluoresce diacetate (DCFH). Meanwhile, the antiproliferative activities was evaluated based on 3-(4.5-Dimethylthiazol-2) -2.5-diphenyltetrazolium bromide (MTT) assay in MCF-7 cells. The results showed that the ethanolic extract of flesh and peel have the ability to reduce oxidative stress and inhibit the proliferation of breast cancer cells MCF-7. The optimum concentration of ethanol extracts of peel in reducing oxidative stress was 200 μg/mL, while that of flesh was 400 μg/mL. Inhibitory concentration (IC50) of cell proliferation of MCF-7 by peel extract was 698.23±1.61 (µg/mL), and flesh extracts was 829.86±5.73 (µg/mL). The ability to reduce and inhibit the proliferation showed a dose dependent manner. There is a high correlation between cellular antioxidant and antiproliferation. The correlation of cellular antioxidant activity of the ethanolic extract of flesh Coleus tuberosus and antiproliferation was 0.93, while the correlation between cellular antioxidant activity ofthe ethanolicextract ofthe peel and anti-proliferation was 0.98. These results suggest that the ethanolic extract of flesh and peel of Coleus tuberosus can be used as a source of natural antioxidants and anti-proliferation.